Spherical fuzzy VIKOR method and Its application to waste management - Kahraman, Cengiz; Karaşan, Ali; GÜNDOĞDU, FATMA KUTLU (My University, 2019)
The extensions of ordinary fuzzy sets such as intuitionistic fuzzy sets (IFS). Pythagorean fuzzy sets (PFS). and neutrosopliic sets (NS). whose mem bership functions are based on three dimensions, aim at collecting experts’ judg ments more informatively and explicitly. In the literature, generalized three-di mensional spherical fuzzy sets have been developed by Kutlu Güııdogdu and Kahraman [3]. including their arithmetic operations, aggregation operators, and defuzzfication operations. Spherical Fuzzy Sets (SFS) are a new extension of In tuitionistic. Pythagorean and Neutrosopliic Fuzzy sets. In this paper, our aim is to employ SF-VIKOR method to waste management problems. We handle a waste disposal site selection problem with five alternatives and four criteria in order to demonstrate the performance of the proposed SF-VIKOR method.
Keywords: Spherical Fuzzy Sets; VIKOR; Waste Disposal; Site Selection